The Effect of Fixed Income And Variable Income on Employee Job Satisfaction Study: PT Barokah Mandiri Jaya - Muhammad Farras Fauzi; Catur Kumala Dewi; Andi Indrawati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze and empirically test the effect of Fixed Income and Variable Income on Job Satisfaction of PT Barokah Mandiri Jaya employees. This study is very important to understand the contribution of various forms of financial compensation in retention strategies and human resource management. This study uses a quantitative approach with a causal design. Primary data were collected through questionnaires distributed to 33 employee respondents. Data analysis was carried out using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method with the help of WarpPLS 8.0 software. The results of the SEM-PLS analysis indicate that Fixed Income and Variable Income have a positive and significant effect on Job Satisfaction, both partially and simultaneously. This finding confirms that the combination of compensation is an effective strategy, where fixed income provides a guarantee of financial stability and security, while variable income (such as incentives and bonuses) serves as a driving factor for motivation and rewards for performance.